A combined approach detected novel species diversity and distribution of dinoflagellate cysts in the Yellow Sea, China. (February 2023) - Liu, Xiaohan; Liu, Yuyang; Chai, Zhaoyang; Hu, Zhangxi; Tang, Ying Zhong
Abstract: Resting cysts of dinoflagellates seed harmful algal blooms (HABs) and their geographic expansion, which makes it fundamentally important to obtain comprehensive inventories of dinoflagellate resting cysts in HABs-prone regions. The Yellow Sea (YS) of China has observed numerous outbreaks of dinoflagellate HABs with some novel species recorded recently indicating an underestimated HABs-causing species diversity. We report our investigation of dinoflagellate cysts of YS via an approach combining metabarcoding sequencing and single-cyst morpho-molecular identification, which identified many novel cyst species and a significant controlling effect of the Yellow Sea Cold Water Mass on cyst composition. The metabarcoding and single cyst-based sequencing detected 11 cyst species never being unambiguously reported in China, 10 never reported as cyst producers, and 3 HABs-causing species never reported from YS. Our detections of many potentially toxic or HABs-causative, particularly novel, cysts and distribution pattern provide important insights into the risks and ecology of dinoflagellate HABs. Graphical abstract: Unlabelled Image Highlights: Many novel and important dinoflagellate resting cysts identified from Yellow Sea, China. Detected 11 and 10 species of cysts having not been confirmed presence from China and as cyst producers, respectively. Cyst distribution patterns differed between the offshore and nearshore areas. The Yellow Sea Cold Water Mass observed to affect the species composition of dinoflagellate cysts. Longitude, latitude, temperature, salinity, and water depth all affected cyst distribution pattern.